PERBANDINGAN HASIL BELAJAR IPS TERPADU MENGGUNAKAN MEDIA ICT DAN MEDIA VISUAL - Dwi Rahmawati; Yon Rizal; Darwin Bangun (FKIP Unila, 2014)
This research aims to know the difference of students’ learning results in IPS Terpadu subject and the effectiveness between the use of ICT media and visual media in IPS Terpadu subject at the ninth grade students of SMP Kartika II-2 Bandar Lampung. This research is an experimental research method with a comparative approach. The population in this research were 131 students and the sample was two classes which divided into 44 students of experiment class and 43 students of control class. The sample was taken by using cluster random sampling. The data were collected by using observation, documentation and test. The data were analyzed by using T-test Two Sample Independent and Formula of N-Gain. The result of this research showed that: (1) The average of students’ learning results in IPS Terpadu subject who taught by using ICT is higher than who taught by using visual media, (2) There is a difference of effectiveness between the use of ICT media and visual media. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar IPS Terpadu siswa dan perbedaan efektivitas antara media ICT dengan media visual pada mata pelajaran IPS Terpadu siswa kelas IX di SMP Kartika II-2 Bandar Lampung. Penelitian ini menggunakan metode penelitian eksperimen dengan pendekatan komparatif. Populasi dalam penelitian ini berjumlah 131 siswa dan sampel sebanyak dua kelas yang terdiri dari 44 siswa kelas eksperimen dan 43 siswa kelas kontrol. Sampel diambil menggunakan cluster random sampling. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan tes. Analisis data menggunakan T-test Dua Sampel Independen dan rumus N-Gain. Hasil penelitian ini menunjukkan bahwa: (1) Rata-rata hasil belajar IPS Terpadu siswa yang diajar menggunakan media ICT lebih tinggi dibandingkan dengan siswa yang diajar menggunakan media visual, (2) Ada perbedaan efektifitas antara media ICT dan media visual. Kata kunci : hasil belajar, ict, visual.